Pengaruh Kepemimpinan, Beban Kerja dan Diklat Terhadap Kinerja Karyawan dengan Lingkungan Kerja sebagai Variabel Intervening pada Perumda Air Minum Tirta Kepri - Astriana, Dona; Indrayani, Indrayani; Satriawan, Bambang (Universitas Batanghari Jambi, 2024)
This research aims to find out: (1) whether leadership, workload, and training have an effect on the work environment; (2) whether the work environment, leadership, workload and training have an effect on employee performance; and (3) whether leadership, workload and training influence employee performance through the work environment. This research was conducted at Perumda Air Minum Tirta Kepri with a population of 121 respondents from Perumda Air Minum Tirta Kepri. Data was collected using a questionnaire method with a questionnaire instrument. Variable measurement was carried out using a Likert scale. The research results found that leadership had a negative and insignificant effect on the environment; workload has a positive and significant effect on the work environment; training has a positive and significant effect on the work environment; work environment has a positive and significant effect on employee performance; leadership has a positive and significant effect on employee performance; workload has a negative and significant effect on employee performance; training has a positive and significant effect on employee performance; work environment has a negative and insignificant influence in mediating leadership on employee performance; work environment has a positive and significant influence in mediating workload on employee performance; The work environment has a positive and insignificant influence in mediating training on employee performance at Perumda Air Minum Tirta Kepri.